THE STATE OF PEROXIDE LIPID OXIDATION IN RATS WITH PERIODONTITIS ON THE BACKGROUND OF HYPER- AND HYPOTHYROIDISM - Shcherba, V.V.; Krynytska, I.Ya.; Cherkashyn, S.I.; Machohan, V.R.; Stoikevych, H.V.; Korda M. M. (World of Medicine and Biology, 2018)
Objective – to study the indices of peroxide oxidation of lipids in rats with periodontitis without concomitant pathology and against the background of hyperthyroidism and hypothyroidism. Materials and methods. The study was performed on 48 white male rats. The experimental animals were divided into the following groups: І – control animals; ІІ – animals with periodontitis; ІІІ – animals with periodontitis combined with hyperthyroidism; IV – animals with periodontitis combined with hypothyroidism. The intensity of peroxide oxidation of lipids (contents of hydroperoxides and TBA-active products) was estimated by the commonly used methods. Results and discussion. A significant increase in the content of TBA-AP in the supernatant of erythrocytes hemolysates was established: in rats with a modeled periodontitis by 2.1 times, in rats with periodontitis in the background of hyperthyroidism - 2.5 times, in rats with periodontitis in the background of hypothyroidism - 2.2 times vs control group. In the homogenate of periodontal tissues, the content of TBA-AP increased more intensively: in rats with simulated periodontitis by 2.6 times, in rats with periodontitis in the background of hyperthyroidism - 3.0 times, in rats with periodontitis in the background of hypothyroidism - 2.4 times vs control group. Conclusions. Thus, the experimental periodontitis is accompanied by a marked increase in the intensity of the processes of lipids peroxide oxidation both in the homogenate of periodontal tissues and in the blood. Imbalance of thyroid hormones increases oxidative stress in experimental periodontitis, especially expressed in hyperthyroidism.